Settlement behaviors of existing tunnel caused by obliquely under-crossing shield tunneling in close proximity with small intersection angle. (March 2020) - Lai, Hongpeng; Zheng, Haiwei; Chen, Rui; Kang, Zuo; Liu, Yang
Abstract: As an increasing number of metro tunnels are being constructed in congested urban areas, it is inevitable that new tunnels are being constructed in close proximity to existing tunnels. The settlement behaviors of existing tunnel caused by under-crossing tunneling have been intensively investigated; however, settlement characteristics of an existing tunnel caused by under-crossing tunneling in close proximity with small intersection angle is rarely explored. To fill this gap of knowledge, this paper presents a special case study of a shield tunnel obliquely constructed in close proximity to an above existing tunnel with a small intersection angle. Based on monitoring data and numerical simulations using finite difference method (FDM), the settlement characteristics of the existing tunnel were studied. The field monitoring data indicates that the deformation of existing tunnel caused by shield tunneling underneath was dominated by vertical settlement, accompanied by torsional deformation. The existing tunnel experienced the largest settlement and torsional deformation in the intersection zone. The numerical simulation results confirm that existing tunnel tracks experience vertical settlement and torsional deformation, which are in line with the field monitoring results; the settlement trough of existing tunnel becomes increasingly wide and deep with advancement of the under-crossing tunneling. The position of the maximum settlement moves in the direction of tunnel advancing but ultimately stays still in the intersection zone.